PEMBERDAYAAN IBU-IBU PKK DESA JUNGSEMI, KECAMATAN KANGKUNG, KABUPATEN KENDAL MELALUI PELATIHAN PENGOLAHAN SEMPRONG JAGUNG - Fafa Nurdyansyah; Rosalina Ginting; Maftukin Hudah; Valdyan Drifanda; Arief Rakhman Affandi (LP4MK STKIP PGRI Lubuklinggau, 2021)
Jungsemi Village is one of the villages located in Kangkung District, Kendal Regency, Central Java which has resource potential, especially agricultural products in the form of corn. The Community Service Team from the University of PGRI Semarang strives to empower the potential in the village through training activities for making semprong made from corn flour produced by local communities, as well as simple product packaging training and followed by online marketing training activities using applications and media social. This activity was attended by community partners, namely PKK Jungsemi Village women for several stages. The results of the activity showed that there was an increase in the skills of the partner community of more than 80% based on the survey results and the community was considered very enthusiastic in participating in this activity. To support the sustainability of this program, the service team continues to monitor and evaluate post-service activities by monitoring partner activities.